Factors Associated with Monocyte and SuPAR Levels in Pulmonary Tuberculosis Patients: A Longitudinal Study - Lalu Ramzy Rahmanda; Agung Tri Utomo; Nur Ikhwana; Annisa Syalsabila (ARRUS Journal of Mathematics and Applied Science, 2026)
Tuberculosis in Indonesia had the second highest TB burden globally, after India. 92% of the estimated cases were confirmed to be pulmonary tuberculosis. However, controlling pulmonary tuberculosis relies heavily on accurate diagnosis, appropriate treatment, effective monitoring, and evaluation. This study aims to model and investigate the most significant factor affecting monocyte and suPAR levels as a biomarker based on observation time, body mass index, and erythrocyte sedimentation rate. This study was a longitudinal study. 60 patients were involved every two weeks over 13 periods. Path analysis with the generalized linear mixed model (GLMM) approach and comparing three estimation methods to investigate the longitudinal relationship between variables and compare the best structure for modeling the relationship. The best model for describing the relationship between observation time, body mass index, and erythrocyte sedimentation rate on monocyte and suPAR levels is GLMM with unstructured covariance (R2 = 0.977 and AIC = 0.052). A significant positive correlation between monocyte and suPAR levels further validates suPAR as a robust biomarker for monitoring treatment response. The study concludes that effective clinical management of pulmonary tuberculosis requires an integrated strategy that combines OAT with regular monitoring of BMI, ESR, and monocyte levels to optimize patient recovery.